Signifikansi Pembelajaran Adab dalam menuntut Ilmu di Era Modern: Studi Komparatif antara Pemikiran Al-Ghazali dan Al-Attas - Mohammad Fauzi Maulana. S (Gunung Djati Conference Series, 2023)
This study aims to discuss the importance of adab learning in studying in the modern era. In this study the authors used a qualitative approach by applying the method of literature study and literature study. The formal object of this research is the thinking of al-Ghazali and al-Attas, while the material object is adab learning related to morality in studying. The rest, the context of this research is in the modern era. The results and discussion in this study indicate that adab is defined as one of the important prerequisites for seekers of knowledge and to whom knowledge is given. The concept of adab is of course in accordance with the terms and objectives of Islamic education, namely the meaning of the word ta'dib whose purpose is to form civilized humans (insan adaby). According to al-Attas, learning adab in studying knowledge can be improved from an attitude of sincerity and honesty in intentions. Meanwhile, al-Ghazali emphasized that cleansing the heart of a student of knowledge is the main task in studying. Like al-Attas's thought, it appears that al-Ghazali also places sincerity as the second obligation after cleaning the heart, namely sincerity in studying. This study concludes that adab makes a person's morals good and the key to improving adab and morals is to cleanse one's heart and have a sense of sincerity in intentions, be honest, and respect each other between someone who teaches knowledge (teacher) and a student of knowledge (student).